Revenue elasticities in euro area countries - Gerrit Koester; Christoph Priesmeier (European Central Bank (ECB), 2017)
Revenue elasticities play a key role in forecasting, monitoring and analysing public finances under the European fiscal framework, which largely builds on cyclically adjusted indicators. This paper investigates whether there is evidence for dynamic – instead of the currently used static – elasticities in euro area countries. Applying country-specific error correction models we reveal important differences across countries. For a majority of euro area Member States we find evidence for dynamic revenue elasticities. We show that the application of such dynamic elasticities could substantially reduce forecast errors in several countries – with the evidence being stronger based on ex-post than based on real-time data.
Keywords: E62; H68; 330; error correction models; EU fiscal surveillance; real-time data; revenue elasticities; tax forecasts